THE DRAMATIC STRUCTURE OF TOURISM ADVERTISEMENT “WONDERFUL INDONESIA EPISODE TORAJA-MAKASSAR” - Afrianto, Damar Tri; Santiko, Putut Bayu (Capture : Jurnal Seni Media Rekam, 2020)
The study of digital advertisement of the tourism was based on the potential of dramatic elements seen in the "Wonderful Indonesia episode of Toraja-Makassar"  advertisement released by the Ministry of Tourism of Republic Indonesia. This research uses the approach and theory of William Wells’s advertising video and Gustav Freytag's dramatic structural theory. The results of this study indicate that important elements in the "Wonderful Indonesia episode Toraja-Makassar" included Rambu Solo', Masilaga Tedong, creative process of weaving, carving, and Tau-Tau sculpture. Voice over in audio uses English. Talent is very good at material. Advertising props contains of South Sulawesi tourism destinations. Setting of advertisement video located in cultural centers in South Sulawesi. Lighting uses soft light and hard light. The graph varies by using long shots, and close ups. Pacing is in normal speed. This ads presents a coherent structure starting from exposition, conflication, climax, conclusion and resolution. In addition, the advertising scenario is packed close to the reality, so that the audience is carried away to the real life This is able to motivate the North Toraja government to create tourism promotion content through video ads that are more attractive.